PENGARUH SUBSTITUSI PENGGUNAAN TEPUNG KEONG MAS TERHADAP KONSUMSI PAKAN DAN KUALITAS PRODUKSI TELUR AYAM ARAB - Akhadiah Afrila; Karunia Setyowati Suroto; Eka Fitasari (BUANA SAINS, 2015)
Pomacea canaliculata Lamarckis a land water snail,knowing as gold snail, that famously knowed as pestin the rice plant since 10 day age after transplanted. Harvest loss because this animal decreasing ricemild (gabah) range 16-40%. Arabian chicken (Gallus turcicus) basicly one ofnative chicken (buras) that already adapted it could be layed280 eggs and people consider that Arabian chicken egg is native chicken egg. The research was done to determine the precentage of gold snail powder (as alternative feed) that would give the best feed consumption andegg production quality. Field research used Completely Randomized Design replication with substitution of control feed with gold snail powder including P0 (basic/control feed without gold snail powder), P1 (97.5% control feed + 2.5% gold snail powder), P2 (95% control feed + 5% gold snail powder), P3 (92.5% control feed + 7.5% gold snail powder), and P4 (90% control feed + 10% gold snail powder), each treatments was repeatedly 5 times and if there were significant effect it would continued by Least Significant Different. The research showed that the using of gold snail powder doesn’t gives significant effect on feed consumption and FCR (feed convertion ratio). More higher of gold snail powder substitution couse the colour of egg yolk become tough, and also the egg heavy, egg diameter, and eggshell thickness become hight, but more highergold snail powdercousing the decreasing of egg yolk fat.10%.Gold snail powdersubstitution show the the best result on egg yolk colour, egg yolk fat, and higher eggsheel. It is suggested continued research usinggold snail powder more than 10% in feed formulation but giving attention on protein and energy balancing, and mineral content not decrease egg production.